The effectiveness of management styles in Iloilo City fast food chains as measured by workers' enthusiasm - Anas, Rhodora; Basco, Kent; Bautista, Katharine; Navarra, Paulo Peter; Vergabera, John Paul
Summary - This paper was made to determine the most effective management style to increase the enthusiasm of team members in fast food chains in SM City, and in Robinson's Place. It aimed to know what management styles are used in the different fast food chains in SM City and in Robinson's Place, Iloilo City. The paper would like to determine how the team members rate these respective management styles. More so, it wants to find out how these management styles affect the job enjoyment of the team memebers. The relationship between job enthusiasm and work enjoyment was also determined, if any. Lastly it wants to determine the best management style in increasing the work enthusiasm of the team members. Using the descriptive type of statistics the study sought to know how team members perceive the excellence of their respective managers. Thechi-square test and cross tabulation through SPSS were employed. Also the enjoyment of the respondents towards their job was considered to further establish its relationship to their level of enthusiasm. Specifically the study aims to help the fast food chain managers in pointing out what type of management to apply to maximize their labor respource. McDonalds-SM City, Chowking-SM City, and Kentucky Fried Chicken-Robinson's Place, were found to be using the executive type. The three other companies, which are Kenny Roger's - SM City, Kentucky Fried Chicken-SM City, and Pizza Hut-Robinson's Place, were using the semi-autocrat type. The study was able to establish a direct relationship between job enjoyment and work enthusiasm. Another significant finding was that the executive type of management style was most effective in increasing the job enjoyment and work enthusiasm of the team members. The recommendation talked about some features of an executive type of management style.